2017
DOI: 10.1016/j.ihj.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the 2013 ACC/AHA cholesterol guidelines on contemporary clinical practice for patients with atherosclerotic coronary and peripheral arterial disease

Abstract: Application of the ACC/AHA guidelines results in a higher percentage of patients considered to be 'at goal' when compared to the ATP III guidelines without changes in clinical practice. This is due to patients ≤75 years old on adequate statin doses but still have LDL-C levels >100mg/dl, thereby raising concerns that physicians may not pursue alternate LDL reduction strategies since they are now considered at goal despite LDL-C >100mg/dl. Lipid management of PAD patients remains sub-optimal as compared to CAD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…The 2013 American College of Cardiology/American Heart Association American Adult Guidelines for the Reduction of Atherosclerosis Lipids recommend low-density lipoprotein cholesterol (LDL-C) <1.8 mmol/l (20).…”
Section: Diagnosis Of CImentioning
confidence: 99%
“…The 2013 American College of Cardiology/American Heart Association American Adult Guidelines for the Reduction of Atherosclerosis Lipids recommend low-density lipoprotein cholesterol (LDL-C) <1.8 mmol/l (20).…”
Section: Diagnosis Of CImentioning
confidence: 99%
“…1,2 Various literature have explored the impact of the 2013 ACC/AHA guidelines on US cardiovascular practices, including physician prescribing patterns, 3−5 changes in patient's adherence to and initiation of statin therapy, 6,7 and implications for defining treatment targets. 8 The majority of these analyses have concluded that a large proportion of statin-eligible patients are not receiving guideline-recommended lipid-lowering therapy after an acute cardiovascular event; however, the reasons for this deficit largely remain unknown. This study used detailed electronic medical records (EMR) and chart review data to establish a more comprehensive understanding of blood cholesterol management practices in a broad sample of patients with acute ASCVD and the reasons for high-risk patients not being treated in accordance with recent guidelines, as documented by the prescribing physician.…”
mentioning
confidence: 99%
“…Dyslipidemia has been considered an important risk factor for atherosclerosis. 13 Existing studies have shown that cholesterol is closely related to the occurrence and development of PAD. In the formation and development of atherosclerosis, LDL-C plays an important role.…”
Section: Discussionmentioning
confidence: 99%